2011
DOI: 10.3749/canmin.49.4.947
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Evolution of Zirconium Mineralization in Peralkaline Granites and Associated Pegmatites of the Khan Bogd Complex, Southern Mongolia

Abstract: The western part of the Khan Bogd complex, in the south Gobi desert, southern Mongolia, comprises (in order of emplacement): microcline-phyric granite, peralkaline aegirine-arfvedsonite granite (main intrusive phase) and aplite-pegmatite veins confined predominantly to the apical parts of the intrusion. These rocks are interpreted to represent products of extreme fractional crystallization involving alkali feldspar, quartz and, to a lesser extent, ferromagnesian silicates and, in the final stages of magma evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Primitive mantle-normalized incompatible trace element abundances of the peralkaline granitic rocks. (d) Bokan granites with relatively flat to slightly LREE enriched patterns; (e) Bokan granites with LREE enrichment and a positive MREE/HREE slope; (f) Typical peralkaline granites: Egypt -average of peralkaline granites of eastern Egypt (Abdel-Rahman, 2006), Mong -average of the main phase granite of the Khan Bogd complex, southern Mongolia (Kynicky et al, 2011), Lac -peralkaline granite of the Lac Brisson, Labrador, Canada (Linnen and Cuney, 2004;Pillet et al, 1992); Khald -average of mineralized granite of the Khaldzan-Buregtey complex, western Mongolia (Kovalenko et al, 1995). Normalizing values are after Sun and McDonough (1989).…”
Section: Magma Evolutionmentioning
confidence: 99%
“…Primitive mantle-normalized incompatible trace element abundances of the peralkaline granitic rocks. (d) Bokan granites with relatively flat to slightly LREE enriched patterns; (e) Bokan granites with LREE enrichment and a positive MREE/HREE slope; (f) Typical peralkaline granites: Egypt -average of peralkaline granites of eastern Egypt (Abdel-Rahman, 2006), Mong -average of the main phase granite of the Khan Bogd complex, southern Mongolia (Kynicky et al, 2011), Lac -peralkaline granite of the Lac Brisson, Labrador, Canada (Linnen and Cuney, 2004;Pillet et al, 1992); Khald -average of mineralized granite of the Khaldzan-Buregtey complex, western Mongolia (Kovalenko et al, 1995). Normalizing values are after Sun and McDonough (1989).…”
Section: Magma Evolutionmentioning
confidence: 99%
“…As noted by Macdonald et al (2016), the HaldzanBuragtag deposit has certain features in common with other peralkaline granitic intrusions which host significant abundances of rare-metal minerals, such as Amis, Namibia (Schmitt et al 2002), Tamazeght, Morocco (Salvi et al 2000), Strange Lake, Canada (Salvi and Williams-Jones 2006;Gysi et al 2013), and Khan Bogd, Mongolia (Kynický et al 2011). These features include evidence for the presence of late-stage Ca and HREE metasomatism.…”
Section: Sequence Of Mineral Assemblagesmentioning
confidence: 92%
“…Owing to a recent increase in the demand for these metals, they are the focus of exploration by mining companies, particularly in the western hemisphere. Studies of rare-metal deposits associated with peralkaline igneous rocks have shown that the mineralization results from igneous or hydrothermal processes, although in most cases both processes played a role in mineralization Williams-Jones, 1990, 2006;Kovalenko et al, 1995;Kempe et al, 1999;Schmitt et al, 2002;Kynicky et al, 2011;Sheard et al, 2012;Gysi and Williams-Jones, 2013). Thus, a topic of some debate is the relative importance of these two processes.…”
Section: Introductionmentioning
confidence: 94%